Penerapan Metode Peer Tutoring untuk Meningkatkan Pemahaman Konsep Matematika Siswa - Aprilia Loisita Kaensige (INTELEKTIUM, 2022)
The study by researcher on student' difficulties in understanding mathematical concept that are taught. Based on the data above, teacher plans the implementation of peer tutoring methods to increase the understanding of mathematical concept. Increase in understanding of the mathematical concept that student uses the design of Classroom Action Research (CAR) models Kemmis and Mc. Taggart. The study was conducted on September 30th, 2022 to November 30th, 2022 in three cycles with a number of 18 student. Instrument used in this research, namely the observation sheet, student questionnaire, interview teacher as a observer, feedback sheet, student test sheet, and document in the form of a list of student' grades. Based on the research, it can be concluded that peer tutoring method can improve student' understanding of mathematical concept. Implementation of peer tutoring is done through a process of guidance for tutors, then tutor guides tutee in understanding the concept of straight line equation..